Authentic leadership's effect on customer orientation and turnover intention among Portuguese hospitality employees: The mediating role of affective commitment. Issue 6 (9th April 2020) - Ribeiro, Neuza; Duarte, Patrícia; Fidalgo, Jessica
Abstract : Purpose: Hospitality employees' attitudes and behaviors play a crucial role in enhancing customer satisfaction and service quality and ultimately firms' success; therefore, organizations must have skilled, customer-oriented staff. More research is required to help hospitality managers gain insights into the best strategies to promote and retain customer-oriented employees. This study specifically sought to provide a more comprehensive understanding of the ways that authentic leadership (AL) can affect employees' customer orientation and turnover intention, including exploring affective commitment's (AC) potential mediating role. Design/methodology/approach: The sample included 350 employees from different hospitality organizations in Portugal. Data were collected using anonymously completed structured questionnaires available online or in a paper-and-pencil format. Findings: The results demonstrate that AL has a positive effect on customer orientation and a negative effect on turnover intention. Moreover, they indicate that AC mediates the relationships between AL and both customer orientation and turnover intention. All hypotheses received empirical support. Practical implications: Hotel managers can increase employees' AC and customer orientation by engaging in AL behaviors. Similarly, management can avoid having employees voluntarily leave their jobs using more AL styles and strengthening employees' affective bonds to their organization. Originality/value: Prior hospitality studies have rarely focused on AL. This study is the first to analyze AL's effect on customer orientation and AC's role as a mediator variable in the relationships between AL and customer orientation and turnover intention, thus integrating all these variables into a single research model.